PENGUNGKAPAN KONSEP MEMERKOSA DALAM SURAT KABAR LAMPU MERAH-LAMPU HIJAU - Mochammad Asyhar (LITERASI: Indonesian Journal of Humanities, 2011)
The use of one of the lexical items from perkosa lexeme in daily newspaper can be related to taboo expressions. One of the efforts made to avoid its usage is by replacing perkosa lexeme with words or group of words that have softer senses. Such a way is taken by Lampu Merah daily newspaper (Lampu Hijau now) published in Jakarta. In regard to this, this article elaborates 36 words and 3 groups of word substituting perkosa lexeme and explains the lexical relations among them. The lexical relation here is the paradigmatic relation. Substitutes and the ways of substituting would be analyzed in this article. Keywords: lexical relation, paradigmatic, subtitution